2005
DOI: 10.1093/ndt/gfi087
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron supplementation for the treatment of anaemia in pre-dialyzed chronic renal failure patients

Abstract: Intravenous iron therapy in pre-dialysis patients with no Epo seems often to ameliorate the anaemia, avoiding the necessity of Epo or blood transfusions in one-third of pre-dialyzed non-diabetic patients. Intravenous iron supplementation appears to be an effective and safe treatment for anaemia in pre-dialysis CRF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 17 publications
6
82
2
3
Order By: Relevance
“…IV iron overcomes this reduced ability to absorb iron [6,20]. Used in isolation, IV iron leads to a significant rise in Hb concentrations in the order of 0.6–2.7 g/dl [21]. In our study, we saw a similar rise (fig.…”
Section: Discussionsupporting
confidence: 78%
“…IV iron overcomes this reduced ability to absorb iron [6,20]. Used in isolation, IV iron leads to a significant rise in Hb concentrations in the order of 0.6–2.7 g/dl [21]. In our study, we saw a similar rise (fig.…”
Section: Discussionsupporting
confidence: 78%
“…In patients with CKD who are anemic but not in CHF, IV iron alone may also increase the Hb level significantly [66,67,68,69], discouraging the use of ESA altogether in many cases. Although there has been concern about IV iron causing renal disease [70], this has not been confirmed by most studies [58,66,68,69].…”
Section: The Effect Of IV Iron Alone In the Anemia Of Chfmentioning
confidence: 99%
“…Although there has been concern about IV iron causing renal disease [70], this has not been confirmed by most studies [58,66,68,69]. However, IV iron can cause oxidative stress [71], and therefore long-term controlled studies of IV iron are needed to evaluate the effects of IV iron in CKD, as in CHF.…”
Section: The Effect Of IV Iron Alone In the Anemia Of Chfmentioning
confidence: 99%
“…Because MCP-1 has profibrotic properties, negative implications for CKD progression by intravenous iron products have been suggested (100). In patients with CKD, intravenous administration of 100 mg of iron sucrose caused transient proteinuria and urinary excretion (104). In addition, van Wyck et al (52) showed that intravenous iron is at least as safe as oral iron in preserving GFR in anemic patients with CKD.…”
Section: Critical Evaluation Of the Risk Of Iron Administrationmentioning
confidence: 99%